Implementation Of Green Open Space Policy In The Utilization Of Public Space In Medan City - Alamsyah, Bhakti; Wahid, Julaihi (International Journal of Science, Technology & Management, 2025)
Implementation of green open space policy in the utilization of public space in Medan City. Implementation of Green Open Space (RTH) policy in Medan is quite complex, including uneven distribution of RTH, poor facilities and infrastructure, minimal supporting facilities for comfort, and incompatibility with the area of ??land used for RTH. problems. Legally and regulatoryly. This study uses a descriptive approach. The results of this study indicate that: 1. The number and nature of RTH in Medan City have not met the needs of the community. 2. The product of Regional Regulation Number 2 of 2015 concerning Detailed Land Use and Development of Medan City in 2015-2035 is not implemented in accordance with other similar regulations. 3. Participation of the Medan community in making the RTH policy a success is still part of the program.